Konsili Vatikan II Ortodoks atau Anti-Kristus? Ulasan tentang Kritik Kalangan Konservatif terhadap Konsili Vatikan II - Georg Ludwig Kirchberger (Institut Filsafat dan Teknologi Kreatif Ledalero, 2020)
This article is based on a video by a conservative group in Indonesia that describes the position of Archbishop Vigano and has been circulating in Indonesia recently. The video argues that the Second Vatican Council left the true Church of Jesus Christ and created the Antichrist Church. In particular, they reject the teachings set forth in the Nostra Aetate decree regarding the truths contained in non-Christian religions and also the position regarding religious freedom as taught in the Dignitatis Humanae declaration. Because they do not agree with the basic direction of the teachings of the Second Vatican Council, they also demand that all council documents be canceled. This article responds to this conservative position by asserting and showing that the Church of Jesus Christ is not always the same, but Jesus brought a spirit into the world and the people who live according to that spirit must always seek new institutional forms in accordance with the development of society. It is according to this basic view that the conservative position is corrected by showing some of the historical facts and developments of theology throughout the history of the Church. Keywords: Archbishop Vigano; Second Vatican Council; Nostra Aetate; freedom of religion; Church of Jesus Christ